2015
DOI: 10.1371/journal.pone.0135132
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phylogeographic Structures of Wild Radish (Raphanus sativus L. var. raphanistroides Makino) in Japan

Abstract: Coastal plants with simple linear distribution ranges along coastlines provide a suitable system for improving our understanding of patterns of intra-specific distributional history and genetic variation. Due to the combination of high seed longevity and high dispersibility of seeds via seawater, we hypothesized that wild radish would poorly represent phylogeographic structure at the local scale. On the other hand, we also hypothesized that wild radish populations might be geographically differentiated, as has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…10–24) lineages (Fig. 2 ) agreed strongly with previous findings [ 17 ]. These populations entirely corresponded to separate geographic regions.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…10–24) lineages (Fig. 2 ) agreed strongly with previous findings [ 17 ]. These populations entirely corresponded to separate geographic regions.…”
Section: Resultssupporting
confidence: 92%
“…The multi-locus analysis demonstrated that there was robust genetic differentiation between the southern and northern groups, consistent with previous findings [ 17 ]. However, in contrast to a previous study, the present study originally suggested that the two lineages were estimated to have diverged approximately 18,000 years ago, during the LGM period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This inconsistency may be related to the differential focus of the markers or high levels of gene flow [68]. Comparative analysis between bi-parental markers and maternally inherited markers can provide comprehensive insights into population dynamics because cpDNA mutations reflect past changes, while nSSR mutations can provide inferences for recent population events [69]. Thus, differences in genetic patterns and rates of evolution often produce large contrasts between nuclear and organelle genetic diversities under conditions of genetic differentiation [28].…”
Section: Lack Of Genetic Differentiation Between Populationsmentioning
confidence: 99%
“…Various insect vectors evolved longer dispersal distance for pollen, whereas the seeds dispersed by wind traveled less than 10 m albeit in open landscapes [74]. Meanwhile, this different consequence might be related to the type and evolutionary rates of different genome sequences [76]. In general, the evolutionary rate of nuclear genomes transmitted by parents was higher than that of maternally inherited chloroplast genomes [77].…”
Section: Genetic Differentiation and Structure Among R Rex Subsp Rementioning
confidence: 99%